Effect of Successful Implementation of SIPKD and Human Resource Competence in supply chain management and Budget Decision Making (Survey of Local Governments in West Java and Banten Provinces) - Kurniawan Kurniawan; Sri Mulyani; Harry Azhar Azis; Srihadi Winarningsih (International Journal of Supply Chain Management, 2020)
Abstract- This study aims to determine the effect of the successful implementation of SIPKD and human resource competencies on supply chain management and budget decision-making quality. Hypothesis-testing research is conducted using qualitative primary data collected from questionnaires. The total population of the data set was 37 local governments. Structural equation modeling is the analytical method used to measure the successful application of SIPKD and human resource competence on financial statement quality and budget decision-making quality. The results of this study indicate that the successful implementation of SIPKD and human resource competence significantly influence financial statement quality. An improvement in financial statement quality is influenced by the successful implementation of SIPKD, and human resource competencies improve budget decision-making quality.